Analysis of entrepreneurship core competency and curriculum integrated with local culture and products - Djubaedi, Dedi; Rohadi, Tedi; Hidayat, Abas; Kodama, Yayoi (Institute of Advanced Engineering and Science, 2024)
Incorporating entrepreneurship into education is an alternative solution to improve the quality of school graduates. This study aims to deeply analyze some of the components of entrepreneurship core competency and curriculum integrated with several local cultural advantages and local products. The method used to analyze in depth the components used the structural equation model (SEM). The total sample was 180 respondents, with the details being Indonesian public and private high school teachers, curriculum experts, and professional entrepreneurs from Kitakyushu University Japan and IAIN Syekh Nurjati Indonesia. The results show that the entrepreneurial core competencies are significantly related to a curriculum integrated with local culture and products. Path analysis shows that each indicator of entrepreneurial core competence and integrated curriculum with cultural advantages and local products are interrelated and significantly influence each other. Entrepreneurship education is relevant for creating graduates with additional abilities. Curriculum integration of the advantages of local culture and products can also foster students' love for local culture and products as a national identity. The research contributes to providing information and recommendations to teachers and schools about the importance of entrepreneurship core competencies. Besides that, it proves that entrepreneurship learning for high school students is more accessible through the local culture and product approaches.